(untitled) (International Journal of Built Environment and Sustainability, 2017)
Land use, urban development and environmental sustainability have become an interesting research arena as urban development would change the city landscape as well as generate environmental degradation. This paper looks at the missing link between land use planning and urban growth, and it implications for environmental sustainability in a selected sub Saharan Africa city of Kaduna, Nigeria. We assessed urban growth from historical GIS data of the city to evaluate the urban expansion. At the same time, regression analysis was used to established relationship between carbon emission and traffic volume in the city. A city characterized by weak land use planning has created a gap leading to uncoordinated land use planning and uncontrolled physical growth. A steady increase of built up area of 8,400.31 hectares in 1982 to an area of 17,120.5 hectares in 2015 can be a reflection of the presence of uncontrolled urban expansion. The lack of coordination between land use planning and urban growth has resulted to environmental ills within the city. One among the ills, is ubiquitous traffic congestion within the city leading to high carbon (CO2) emission. Findings shows a strong connection between emission and volume of traffic. In addition to findings, is the decline of green areas in the city. By this findings, it is suggested that the modern concept of land use planning which embraces flexibility, public participation and integration of environmental issues should be entrenched and allow to take the lead in the process of urban growth.